2017
DOI: 10.18006/2017.5(1).007.013
|View full text |Cite
|
Sign up to set email alerts
|

Male infertility: screening of azoospermia factor (azf) microdeletion in idiopathic infertile men

Abstract: Genetic factors cause about 15% of male infertility and microdeletions of Y chromosome is one of the genetic causes in idiopathic infertile men. Azoospermia factors (AZFa, AZFb, and AZFc) on Yq long arm are most important for spermatogenesis. For analysis of microdeletions in the AZF regions by sequence-tagged-site (STS) PCR is important screening method for infertility. An attempt has been made to evaluate the frequencies of microdeletions of AZFa, AZFb, AZFc in idiopathic cases of azoospermic and oligozoospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Among all tested STS makers that we used for microdeletions screening, the STS sY254 & sY255 have been identified as most informative and these two cover the DAZ (Deleted in Azoospermia) gene. DAZ , a gene with multiple copy numbers containing several palindromic repetitive sequences in AZFc region, whose reduction of copy number enhances the risk of male infertility (Ambulkar & Pande, 2017 ). In the earlier study, it was evident that the deletions of the DAZ gene marked by sY254 and sY255 are co‐incidental (Krausz et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among all tested STS makers that we used for microdeletions screening, the STS sY254 & sY255 have been identified as most informative and these two cover the DAZ (Deleted in Azoospermia) gene. DAZ , a gene with multiple copy numbers containing several palindromic repetitive sequences in AZFc region, whose reduction of copy number enhances the risk of male infertility (Ambulkar & Pande, 2017 ). In the earlier study, it was evident that the deletions of the DAZ gene marked by sY254 and sY255 are co‐incidental (Krausz et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another study claims 8.5% Yq microdeletions among 340 azoospermic Indian men subjected to analysis (Thangaraj et al, 2003 ). Thorough and consecutive studies from Central India in the years 2014, 2015, and 2017 reported the frequency of Yq microdeletion as 8.33%, 12.8%, and 10.6%, respectively (Ambulkar et al, 2014 ; Ambulkar et al, 2015 ; Ambulkar & Pande, 2017 ). As stated by the previous studies, AZFc appears to be the region most susceptible to deletion in azoospermic or oligozoospermic men.…”
Section: Discussionmentioning
confidence: 99%
“…The global frequency of Y chromosome microdeletions is reported to range from 1 to 55.5% [22]. We found microdeletions in Indian population from a minimum of 0.59% to a maximum of 32.62% with an average of 13.48% [2,[5][6][7][8][9][10][11][12][13][14]. The phenotype associated with AZF deletions varies from azoospermia to normozoospermia depending upon the size of deletion and the genetic background of the population.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies over the last two decades have analyzed Ydeletions in various populations across the world (Fig. 1) and Indian sub-continent [2,[5][6][7][8][9][10][11][12][13][14]. Most of these studies supported the association of Y-deletions with male infertility; however, the frequency of different deletions varied across the studies.…”
Section: Meta-analysismentioning
confidence: 99%
“…Recent studies have discussed the role of abnormalities in men's sperm genomes, such as chromosomal abnormalities, chromatin fragmentation, and microdeletions in the azoospermia factor (AZF) region, on frequent miscarriages in their wives (Pal et al., 2018 ; Tan et al., 2019 ). Infertility has been linked to microdeletions of the Y chromosome in numerous studies (Ambulkar & Pande, 2017 ; Kaminski et al., 2020 ; Liu et al., 2016 ; Pylyp et al., 2015 ), so it is also possible that repeated abortions are related to these microdeletions. The prevalence of AZF region microdeletions in men can vary from 2% to 10%, depending on the society (Zargar et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%